The Contributions of the Arabic Language to Islamic Studies - Arif Widodo (Annusfy : Journal of Multidisciplinary Research, 2026)
This article examines the contribution of Arabic to Islamic studies by positioning Arabic not merely as a medium of communication, but as a theological, epistemological, and methodological foundation for understanding Islam. Using a descriptive qualitative design and library research, this study analyzes primary academic literature on Arabic, Qur'anic studies, hadith studies, fiqh, and uṣūl al-fiqh. The research findings demonstrate that Arabic is indispensable for accessing the primary sources of Islam—the Qur'an and the Sunnah—because core meanings are embedded in its grammatical, morphological, and rhetorical structures. Mastery of naḥw, ṣarf, and balāghah is crucial to avoid semantic reduction and interpretive distortion, especially in distinguishing ‘ām–khāṣṣ, ḥaqīqah–majāz, and amr–nahy, as well as in appreciating the i‘jāz lughawī of the Qur’an. This study also shows that Arabic functions as an epistemic framework that shapes Islamic concepts such as ‘ilm, ‘aql, ḥikmah, and fiqh, thus influencing the standards of authority and validity of knowledge.